Respostas comportamentais (modulações das Descargas do Órgão Elétrico - DOEs) de peixes elétricos pulsadores (Hypopomidae e Rhamphichthyidae, Gymnotiformes) expostos a sinais elétricos interferentes - Petersen, Thiago Alexandre (Instituto Nacional de Pesquisas da Amazônia - INPA, 2021)
The order Gymnotiformes is composed by the Neotropical electric fish. The most distinct feature of this group is the ability to produce and detect electric fields (Electric Organ Discharges - EOD), which allows them to orient themselves, detect objects and communicate. EODs exhibit a precise rhythm, which is coordinated by a pacemaker nucleus, that is located in the fish's brain. Examples of such EOD modulations are complete interruptions of ongoing EODs, gradual frequency rises, or brief abrupt and intense frequency rises, known in Other studies as chirps. Laboratorial experiments allow these behaviors to be explored through responses to electrical stimulation, based on EODs playback, which can be artificially controlled in time or intensity. The gymnotiform families Hypopomidae and Rhamphichthyidae are sister groups, that present several characteristics in common, as weak and a pulse-type EOD. In the òpportunity to describe new behavioral patterns in species not yet tested in the laboratory and the chance to identify basis for behavioral and neurophysiological studies, this work has as main objective to describe and compare the EODs modulations in different genera and species of the family Hypopomidae and Rhamphichthyidae (Gymnotiformes) evoked by electrical stimulus. The focal point of each chapter in this study is organized into: (1) the electrical behaviors of the families studied; (2) description of the EOD interruptions presented; and (3) description of the chirps observed. In chapter 1, two types of experiments with electrical stimulation were performed (11 species: 5 Hypopomidae and 6 Rhamphichthyidae). In these experiments, 14 different responses were categorized, but not all species showed the same repertoire: ranging from 6 to 11 different types of responses per species. In chapter 2, the individuals (14 species: 7 Hypopomidae, 6 Rhamphichthyidae and 1 Gymnotidae) were submitted to several experiments and stimulations, with a total of 165 EOD interruptions in 10 different species (6 Hypopomidae, 3 Rhamphichthyidae and 1 Gymnotidae), which were classified into 4 types (according to the interruptions characteristics). In chapter 3, based on the behaviors obtained in a fixed frequency pulse train electrical stimulations, 3410 behaviors of abrupt and rapid frequency rise (chirps) were obtained in 3 different species (2 Hypopomidae and 1 Rhamphichthyidae). The electrical behaviors observed in this work were explored and described in a qualitative and quantitative way. In relation to the EOD interruption, these presented structures similar to others described in the literature, suggesting a similar neural control between species. The chirps described in this study were similar to others already decribed to other species. The EOD modulation called Tumultuous Rises and an short latency chirp have also been described in this study. Despite the knowledge generated by this thesis, several questions about ecology, behavior and neurophysiology of these groups remain open and should stimulate future research.
Behavioral responses (Electric Organ Discharge modulations - EOD) of pulse electric fishes (Hypopomidae e Rhamphichthyidae, Gymnotiformes) exposed to jamming electric signals
Keywords: Gymnotiformes; Comportamento; Peixes elétricos; DOE; Sinais comunicativos; chirps; Playback; Interrupções de DOE; EOD; Electric fish